2012
DOI: 10.1128/jvi.07244-11
|View full text |Cite
|
Sign up to set email alerts
|

The H275Y Neuraminidase Mutation of the Pandemic A/H1N1 Influenza Virus Lengthens the Eclipse Phase and Reduces Viral Output of Infected Cells, Potentially Compromising Fitness in Ferrets

Abstract: The H275Y amino acid substitution of the neuraminidase gene is the most common mutation conferring oseltamivir resistance in the N1 subtype of the influenza virus. Using a mathematical model to analyze a set of in vitro experiments that allow for the full characterization of the viral replication cycle, we show that the primary effects of the H275Y substitution on the pandemic H1N1 (H1N1pdm09) strain are to lengthen the mean eclipse phase of infected cells (from 6.6 to 9.1 h) and decrease (by 7-fold) the viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
225
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(246 citation statements)
references
References 46 publications
16
225
1
Order By: Relevance
“…τ L ¼ 1=k) from 1 h to 24 h, consistent with previous estimates obtained when fitting models (with normal or lognormal delay distributions for L and I) to in vitro data Pinilla et al, 2012). δ…”
Section: Concentration Of Free Vrna (Present In Both Infectious and Nsupporting
confidence: 81%
See 3 more Smart Citations
“…τ L ¼ 1=k) from 1 h to 24 h, consistent with previous estimates obtained when fitting models (with normal or lognormal delay distributions for L and I) to in vitro data Pinilla et al, 2012). δ…”
Section: Concentration Of Free Vrna (Present In Both Infectious and Nsupporting
confidence: 81%
“…In order to produce more biologically accurate distributions for the latent and infected cell lifespans, the L and I compartments are each split into 20 stages, for both strain A and strain B (Petrie et al, 2013). The model is similar to that used by Pinilla et al (2012) to model competition between co-infecting strains in cell culture.…”
Section: Within-host Co-infection Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers recently found that the H274Y NA substitution in H1N1pdm09 influenza A viruses reduces viral fitness after infection in ferrets, potentially by increasing the eclipse phase of viral growth (i.e., the time between infection and production of infectious virus) (78). In a genetic background without permissive mutations, reduced cell surface NA protein expression could increase the length of time necessary for infectious virus to bud and be released from an infected cell.…”
Section: Discussionmentioning
confidence: 99%